"Molecular insights into the production of few-layer graphene in N-Cyclohexylpyrrolidone + water mixtures". (January 2021) - Nascimento, Jefferson P.; Serodre, Tiago; Santos, Joyce C.C.; Paulinelli, Laura R.; Santos, Adelina P.; Aparício, Santiago; Costa, Luciano T.; Furtado, Clascídia A.
Abstract: The chemical exfoliation of graphite in liquids is the choice method to produce few-layer graphenes with versatility and scalability. While physical mechanisms have been described, the understanding of the graphene-medium interactions at the molecular level is still a challenge. Here, a systematic experimental and theoretical investigation of factors that control the chemical exfoliation of graphite into graphene was performed using 1-cyclohexyl-2-pyrrolidone (CHP)/water mixtures as model systems. The "molecular wedge" structure of CHP and the reduction of graphene-CHP interfacial energy are critical factors in the exfoliation of graphite, but they are not sufficient for the stabilization of the isolated graphene sheets. We propose that such stabilization occurs by steric forces with the formation of a sandwich-like structure on the surface of graphene with two layers of water molecules interleaved with a monolayer of CHP, and by electrostatic forces resulting from the hybrid surface polarization due to the CHP/H2 O-graphene interaction. This stabilization is hampered in CHP/H2 O mixtures containing above 10 wt% CHP due to the formation of CHP–CHP aggregates. Graphical abstract: Image 1